Nanos gigantium humeris insidentes: old papers informing new research into Toxoplasma gondii. Issue 13 (December 2021) - Lodoen, Melissa B.; Smith, Nicholas C.; Soldati-Favre, Dominique; Ferguson, David J.P.; van Dooren, Giel G.
Graphical abstract: Highlights: Seminal papers in Toxoplasma research are revisited. We focus on a paper that contributed to uncovering the complete life-cycle of Toxoplasma. A paper that revealed some of the unique cellular biology of the parasite is examined. A study that elucidated the nature of the compartment in which Toxoplasma resides is described. We revisit a seminal paper in understanding the immune responses to Toxoplasma infection. Abstract: Since Nicolle, Manceaux and Splendore first described Toxoplasma gondii as a parasite of rodents and rabbits in the early 20th century, a diverse and vigorous research community has been built around studying this fascinating intracellular parasite. In addition to its importance as a pathogen of humans, livestock and wildlife, modern researchers are attracted to T. gondii as a facile experimental system to study many aspects of evolutionary biology, cellular biology, host-microbe interactions, and host immunity. For new researchers entering the field, the extensive literature describing the biology of the parasite, and the interactions with its host, can be daunting. In this review, we examine four foundational studies that describe various aspects of T. gondii biology, presenting a 'journal club'-style analysis of each. We have chosen a paper that established the beguiling life cycle of the parasite (Hutchison et al., 1971), a paper that described key features of its cellular biology that the parasite shares with related organisms (Gustafson et al., 1954), a paper that characterised the origin of the unique compartment in which the parasite resides within host cells (Jones and Hirsch, 1972), and a paper that established a key mechanism in the host immune response to parasite infection (Pfefferkorn, 1984). These interesting and far-reaching studies set the stage for subsequent research into numerous facets of parasite biology. As well as providing new researchers with an entry point into the literature surrounding the parasite, revisiting these studies can remind us of the roots of our discipline, how far we have come, and the new directions in which we might head.